Pemberdayaan Masyarakat Desa Melalui Perwujudan "Kampung Seni" - Setyarama, Handri; Muhammad, Yusron Fattah; Redjosari, Slamet Muliono (Journal Pemberdayaan Masyarakat Indonesia, 2024)
This research apart from aims to get an overview of the implementation of community empowerment through embodiment of Kampung Seni, also explains the factors that support and obstacle to the government's work in realizing the empowerment program. This research was conducted with the allocation of time for 20 days, on September 30th to October 20th 2021 and located in Nglumpang Village, Mlarak, Ponorogo. The method used is a qualitative-descriptive research approach field studies. Meanwhile, to uncover and study the implementation process community empowerment program as a whole, the author uses the approach case study. The results of the study show not only as legality and law holders important role of the government in realizing the Art Village, but also marketing and promotion, mobilizer and coaching, as well as a role as a facilitator. Efforts made government, among others: 1) activating youth organization management, 2) increasing the role of youth organizations and the community in the preservation of arts and culture, and 3) increasing productive arts including intensive training and coaching of art studios. Supporting factors Kampung Seni policies are: resource assets, both natural and human resources, level awareness of related parties, cooperation and budget. While the inhibiting factor namely: technological developments, busy players, prestige and lazy culture of children youth, passive participation of the community, and limited means of accommodation.